Persepsi dan pengetahuan siswa terhadap modul ajar ilmu pengetahuan alam (IPA) berbasis augmented reality (AR) - Asri, Eflitha Nurhaqiqi; Hamka, Defrizal (Karoteh Utama, 2021)
This study aims to observe students' knowledge of using Augmented Reality (AR)-based teaching modules in science education through their perceptions. The research employs a quantitative descriptive approach, utilizing questionnaires and interviews as research instruments. Data analysis is conducted using the Interactive Model of Miles and Huberman. This research was conducted in one of the junior high schools in Pekanbaru, with 24 research subjects. This study's findings indicate that most students know about Augmented Reality (AR)-based teaching modules. Most students agree that using AR-based teaching modules as a learning medium assists them in understanding science materials. These findings indicate the positive potential of using AR technology in the context of science education. In the future, this technology integration can be further developed to enrich student's learning experiences and enhance their understanding of scientific concepts. These findings are expected to provide valuable insights for developing technology-based learning strategies in education.